Quality of life among elderly patients with hearing impairment in ORL clinic, Hospital Universiti Sains Malaysia - Rahim, Nur Azureen Abdul (Universiti Sains Malaysia, 2013)
Hearing impairment is a common consequence of aging but unfortunately receives minimal attention. Later, it will affect the quality of life among elderly which could lead to difficulty in communication and lead to depression and social withdrawal. There are a few factors that could lead to hearing impairment such as history of smoking, age, used of gun, occupational noise, and health problems. The aim of this study was to determine the quality of life among elderly who had experienced hearing impairment. Respondents were taken via convenient method among geriatric patients in Othorinolaryngology Clinic Hospital USM, aged 60 years and above and do not used hearing aid. A self- developed questionnaire was used to collect data. Majority of the respondents (66.1%) in this study were between aged 60 to 69 years. The result shows that 90.3% of the respondents had more hearing impairment. Moreover, there was significant relationship between history of smoking with hearing impairment (p= 0.018} meanwhile the others selected socio demographic data were not significant relationship with hearing impairment. The association between physical, cognitive and social scale of quality of life and hearing impairment level was not significant association with coefficient association was r= -0.228. Besides that, there were significant association between Communication Scale of Quality of Life and Psychological Scale with hearing impairment. In conclusion, the hearing impairment had influenced daily communication and gave some stressful event in elderly life. There is need to increase awareness for hearing impairment and the management with program or using media so that quality of life could be improved later